The paleosurface signatures of the Pantingan gold system clues to epithermal gold mineralization in Mt. Mariveles, Bataan, Philippines - Payot, Betchaida Duetes (Quezon City College of Science, University of the Philippines, 2007)
The Pantingan Gold System (PGS) is a vein-type epithermal prospect exposed within the summit caldera of Mount Mariveles, Bagac, Bataan (Luzon), Philippines. It consists of nine major veins, eight of which trend NW-WNW and distributed in an en echelon array. The eastern tips of these veins appear to terminate near the NE-NNE trending Vein 1, which is located in the easternmost portion of the prospect. Metal assay results on vein and wall rock samples indicate concentrations of 0.01 to 1.1 g/t Au, trace to 34 g/t Ag and 0.003 to 0.02 % Cu. Andesite lava flow deposits host the PGS. Potassium-Argon isotopic dating of these andesites revealed a narrow age range of 0.88 ± 0.13 to 1.13 ± 0.17 Ma. The geochemical and petrologic evaluation of the fresh host rock and altered rock samples associated with the PGS also yield several notable observations that are useful in pinpointing potential gold pathfinder elements. Moreover, mass balance calculations also reflected the geochemical observations pertaining to the gains and losses in SiO2. This is largely attributed to silica inundation or leaching. Enrichment of Fe2O3+MgO in the altered samples may be due to sulfide formation. The elevated amounts of CaO+Na2O suggest that despite the breakdown of plagioclase, calcite as verified by petrographic analysis is present in samples. The veins consist of gray to cream-colored crystalline and chalcedonic quartz and amorphous silica. Surface exposures of the veins (up to 5 m wide) are encountered at different levels between 590-740 masl. These commonly display a massive texture although banding prominently occurs in Vein1. Pyrite is the most ubiquitous sulfide mineral. It occurs either as fine-grained disseminations and aggregates in quartz or as infillings in vugs. Calcite, marcasite and bornite are also occasionally noted in the deposit. The prospect shows silicic, argillic, propylitic and advanced argillic alteration zones. Silicic and argillic alterations are confined in the immediate wall rocks of the qualtz veins. Argillic alteration grades to a propylitic zone away from the veins. The advanced argillic alteration zone, indicated by a suite of acidic clay minerals that include kaolinite, dickite, pyrophyllite, and alunite might have been a product of a post mineralization event. Massive silica caps outcrop at elevations between 800-900 masl in the Pantingan Gold System (PGS). These are composed of brownish yellow amorphous silica with disseminations of pyrite ( ~ 1 % of total rock). In addition, boulders of sinter showing grayish - to white thin (< 1cm) silica bands were also encountered along river traverse. Stratigraphic relationships suggest tha these silica bodies overlie the vein type mineralization in the area. It can be said that in the PGS, the presence of paleosurface features further helped in constraining the epithermal mineralization style observed in Mount Mariveles. Moreover, the occurence of the silica capping and sinter indicate that the currently exposed gold-bearing veins could correspond to the top of a more extensive vein system at depth. Further exploration work in the PGS should focus on the possible existence of a bonanza zone below the exposed horizon. Other exploration techniques particularly core driling may be utilized to confirm this.
Vita.
Thesis (M.S. Geology)--University of the Philippines Diliman
Keywords: Paleothermometry -- Mt.Mariveles -- Bataan -- Philippines; Mineralogy -- Research -- Mt.Mariveles -- Bataan -- Philippines